Pengaruh Kualitas Pelayanan dan Lingkungan Kerja Fisik terhadap Kinerja Pegawai Dinas Kependudukan dan Pencatatan Sipil Kabupaten Pasaman dengan Kepuasan Kerja Sebagai Variabel Mediasi - Akmal Akmal; Yulihasri Yulihasri (STIE AMKOP, 2023)
This study aims to analyze the effect of service quality and physical work environment on employee performance with job satisfaction as a mediating variable. This research is motivated by problems with service quality and physical work environment conditions that affect decreased job satisfaction and impact on employee performance at the Population and Civil Registration Office of Pasaman Regency. This research uses a quantitative approach with the Partial Least Square method with the Structural Equation Modeling equation model. Data collection techniques with questionnaires and observation. Respondents to this study were 59 employees of the Population and Civil Registration Office of Pasaman Regency, using the total sampling method where the entire population in this study was used as the research sample. Data processing and hypothesis testing is calculated using the SmartPLS program. The results of this study found that the direct effect of service quality and physical work environment had a positive and significant effect on job satisfaction, job satisfaction and physical work environment had no positive and significant effect on performance and service quality had a positive and significant effect on performance. the indirect effect of job satisfaction as a mediating variable does not have a positive and significant effect between service quality and performance as well as between the physical work environment and the performance of the Pasaman Regency Population and Civil Registration Service Employees. Keywords: Service Quality, Physical Work Environment, Job Satisfaction, Performance